Психологічний стан дітей із надмірною масою тіла та ожирінням - Величко, В. І.; Ерастова, Л. Є. (Clinical Endocrinology and Endocrine Surgery, 2011)
It is important to focus attention on the psychological problems encountered in children with eating disorders, and the study of personality traits of children who are overweight or obese. If child have many unmet needs in situations of emotional discomfort he or she will strive to overcome anxiety, relieve tension and excitement with food. Identifying these physiological changes and behavioral characteristics will help in the individual approach to each child and his family at the stage of a plan of action for therapeutic and prophylactic measures.